Effectiveness of sodium dichloroacetate against glioma с6 depends on administration schedule and dosage - Fedorchuk, A.G.; Pyaskovskaya, O.N.; Gorbik, G.V.; Prokhorova, I.V.; Kolesnik, D.L.; Solyanik, G.I. (Experimental Oncology, 2016)
Background: Anticancer action of sodium dichloroacetate (DCA) could be related to its ability to activate oxidative phosphorylation leading to enhanced generation of reactive oxygen species and induction of apoptosis. On the other hand, activation of oxidative phosphorylation could promote tumor cell survival, in particular, via increased ATP synthesis. Such ambiguous effects of DCA could influence its anticancer effectiveness, depending on biological properties of a tumor, schedule of DCA administration and its dosage. The aim of the study was to analyze anticancer effect of DCA against glioma С6 in rats under conditions of different schedules of its administration and various dosages. Materials and Methods: The study was carried out in Wistar rats with intracerebrally transplanted glioma С6 cells. Therapy with DCA was performed as follows: daily for 6 days starting from the second day after tumor cell transplantation (schedule І) or 7th day (schedule ІІ) at a dose of 1.0 g/kg, or daily for 13 days starting from the second day at doses of 1.0; 1.5 or 4.5 g/kg (schedule ІІІ). An influence of hypoxia on anticancer effect of DCA was studied using hypoxic chambers where oxygen content was maintained at a level of 12.5–13% for 3 h after DCA administration to glioma С6 bearing rats. The state of mitochondrial electron transport chain components in tumor cells was studied using electron paramagnetic resonance. Results: It has been shown that therapy with DCA using schedule I resulted in 15% decrease of animals life span (LS; р < 0.05), while the use of schedule II had no effect on this index. Prolonged administration of DCA (schedule ІІІ) resulted in significant antitumor effect and increased LS of rats by 25.5% (p < 0.05). Under hypoxic conditions, treatment with DCA resulted in a significant increase of animal LS by 15–22%. Dosage of DCA had a moderate effect of its anticancer action. Maximal effect, an increase of LS by 34.5% (p < 0.05) was detected at a dose of 1.5 g/kg. It has been shown that anticancer activity of DCA under all studied conditions is not related to its influence on a functional state of tumor cell mitochondria. Conclusion: Anticancer effect of DCA significantly depends on a schedule of its administration; being administered at equal total dose, but dependent on the schedule DCA could cause ambiguous effects varying from tumor growth stimulation to significant anticancer activity. Under hypoxic conditions, anticancer efficacy of DCA against glioma С6 is significantly enhanced.